HUBUNGAN PENGGUNAAN ALAT KONTRASEPSI HORMONAL TERHADAP PENINGKATAN BERAT BADAN DAN GANGGUAN SIKLUS HAID PADA AKSEPTOR KB DI DESA LAMBHEU KECAMATAN DARUL IMARAH KABUPATEN ACEH BESAR TAHUN 2023 - Aslina, Eja Sri; Saudah, Saudah; Dewi, Rika; Efriana, Cut; Darmawati, Darmawati; Khairina, Ira (Fakultas Kebidanan Institut Kesehatan Deli Husada, 2023)
Data obtained from WHO 2018, family planning is an action that helps individuals or married couples to obtain certain objectives, avoid unwanted births, get births that are desired, contraceptives around the world mostly use Injectables 35.3%, Pills 30.5%, IUDs 15.2%, Implants 7.3% and other contraceptives 11.7%. The use of hormonal contraceptives causes side effects including changes in menstrual patterns, weight changes. The purpose of the study was to determine the effect of using hormonal contraceptives on weight gain and menstrual cycle disorders in family planning acceptors in Lambheu Village, Darul Imarah District, Aceh Besar Regency in 2023. This research method is Descriptive Quantitative with Linear Regression approach with Purposive sampling technique with a sample size of 87 respondents. This research was conducted on June 11 to 14, 2023 in Lambheu Village, Darul Imarah District, Aceh Besar Regency, with univariate and bivariate analysis. The results showed that there was an effect of the use of contraceptive pills, injections and implants on weight gain with a sig test result of 0.066 and menstrual cycle disorders with a sig test result. 0,057. Conclusion There is an effect of using Hormonal Contraceptives on increasing Body Weight with Linear Regression test Sig value. 0,066 < 0,05. There is an effect of the use of Hormonal Contraceptives on menstrual cycle disorders with a Linear Regression Test Sig value. 0,057 < 0,05.